Deep-water processes and facies models : implications for sandstone petroleum reservoirs - Shanmugam, G. 1944- (Handbook of petroleum exploration and production ;, 2006)
This rock-based book is an attempt to link deep-water process sedimentology with sandstone petroleum reservoirs. In presenting a consistent process interpretation, the author has relied on his description and interpretation of core and outcrop (1:20 to 1:50 scale) from 35 case studies (which include 32 petroleum reservoirs), totaling more than 30,000 feet (9,145 m), carried out during the past 30 years (1974-2004). This book should serve as an important source of information for students on history, methodology, first principles, advanced concepts, controversies, and practical applications on.